The zombification of the economy? Assessing the effectiveness of French government support during COVID-19 lockdown - Mattia Guerini; Lionel Nesta; Xavier Ragot; Stefano Schiavo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
This paper evaluates the risk of zombification of the French economy during the sanitary crisis, as a result of the unconditional financial support provided to firms by public authorities. We develop a simple theoretical framework based on a partial-equilibrium model to simulate the liquidity and solvency stress faced by a large panel of French firms and assess the impact of government support measures. Simulation results suggest that those policies helped healthy but illiquid firms to withstand the shock caused by the pandemic. Moreover, the analysis finds no evidence of a "zombification effect", as government support has not disproportionately benefited less productive companies.
Keywords: H12; H32; J38; G33; L20; 330; Covid-19; zombie firms; job-retention schemes; microsimulation; policy evaluation